An ethnopharmacological survey and comparative analysis of plants from the Sudhnoti District, Azad Jammu and Kashmir, Pakistan - Muhammad Faraz Khan; Zia-; Ansar Mehmood; Rehmatullah Qureshi; Rizwan Sarwar; Khawaja Shafique Ahmad; Cassandra L. Quave (BMC, 2021)
Abstract Background This is the first comprehensive report on the traditional and novel uses of medicinal plants practiced by the indigenous communities of the Sudhnoti district of Azad Jammu and Kashmir (AJK), Pakistan. The area is rich in folklore and indigenous medicinal knowledge due to a unique tribal composition and socioeconomic conditions. This study aimed to document traditional knowledge of native plant use by the local communities, particularly those used for therapeutic purposes. Methods Field surveys were conducted from September 2015 to March 2017. Interviews with 125 local inhabitants of different tribes, age groups, genders, and occupations were conducted using structured and semi-structured questions along with group discussions. Data gathered on plant uses, local names, and modes of application of each plant species were organized in tables. Ethnobotanical indices such as use value (UV) and cultural significance index (CSI) were used to produce quantitative information on the plant use category, frequency, and cultural preference of species. Reports on therapeutic uses of medicinal plants were compared with previous studies. Results In all, 88 plant species from 45 families were reported, out of which 67 (77%) were used in ethnomedical applications. Asteraceae, Rosaceae, Fabaceae, and Lamiaceae were the dominant families. Berberis lycium was the most valued plant species, followed by Zanthoxylum armatum and Taraxacum officinale. Mentha arvensis had the highest cultural significance, followed by Mentha longifolia, Punica granatum, and Zanthoxylum armatum. Leaves were the most preferred plant parts in the preparation of medicine exclusively or mixed with other parts. The most frequently used process of crude preparation of medicinal plants was cooking. Oral intake was the predominant route of administration. Conclusions Our comparative analysis confirmed that most of the plants documented have uses that match those previously reported for the region and other parts of the world, with the exception of novel medicinal uses for 11 plant species, including Verbascum thapsus for earache, Elaeagnus umbellata for hepatitis, Achillea millefolium for oral care, Dicliptera roxburghiana to prevent sunstroke in cattle, Rumex hastatus for allergy antidote, Pyrus pashia for hepatitis, and Nerium oleander for diabetes.